'A Different World': Dorothy K. Haynes's Domestic Horror. Issue 1 (March 2022) - Baker, Timothy C.
Abstract : Throughout Dorothy K. Haynes's work Scotland is presented as uniquely infused with the supernatural and tied to the ballad tradition. Although Haynes published widely in the middle decades of the twentieth century, and her work was republished in two 'best of' collections in 1981 and 1996, her stories remain underexamined. At her best, Haynes might be thought of as Scotland's answer to Shirley Jackson; her work is characterised by a prevailing sardonic humour and matter-of-fact approach to supernatural events. Haynes, however, approaches her Scottish setting in two very distinct ways. In her historical stories, often centring on witch trials, the physical landscape is richly described, and at times appears to have a haunting agency of its own. Her stories with contemporary settings, on the contrary, focus primarily on domestic interiors. In many of these stories, such as 'Double Summer Time', 'The Nest', and 'The Wink', the natural world is an intrusive, disruptive force. Examining such stories alongside more famous tales of the everyday supernatural, including 'The Peculiar Case of Mrs Grimmond', reveals the complexity of Haynes's approach to the supernatural, which challenges oppositions between familiar and unfamiliar, natural and supernatural and interior and exterior. Haynes's work reshapes the Scottish environment to show the instability of modern life, and the prevalence of older forms of storytelling and enmeshment in the natural world.